Cognitive, Conative and Behavioral Neurology An Evolutionary Perspective - Hoffmann, Michael (Springer International Publishing : Imprint: Springer, 2016)
This ground breaking title presents the many different neurologic syndromes and vastly expanding data in the brain sciences from an evolutionary, or neuro-archeological, perspective, as well as a clinical one. The neuro-archeological perspective offers a more thorough picture of the field - providing hindsight that leads to great insight and foresight. It thus provides the reader with the core foundational aspects of many perplexing neurologic syndromes. Authored by a noted authority in cognitive neurology and including ample tables, diagrams and images, the book covers the full range of behavioral neurological, psychological and neuropsychiatric syndromes, as well as their underlying disease states, relevant neuropsychological tests and contemporary neuroimaging, both structural and functional. The evolutionary approach offers a comprehensive, novel, and completely updated overview of each topic. An invaluable title unlike any other in the field, Cognitive, Conative and Behavioral Neurology: An Evolutionary Perspective is a landmark resource and will be of great interest to neurologists, psychiatrists, neuroscientists, and trainees in all fields. .